Association of academic stressors with sleep disturbances in medical students: is psychological stress a mediator? - Waqas, Ahmed; Khan, Spogmai; Sharif, Waqar muhammad; khalid, Uzma; Ali, Asad (PeerJ PrePrints, 2014)
Introduction: Medicine is one of the most stressful fields of education because of its highly demanding professional and academic requirements. Psychological stress, anxiety, depression and sleep disturbances are highly prevalent in medical students. Methods: This cross-sectional study was undertaken at CMH Lahore Medical College and Institute of Dentistry in Lahore, Pakistan, and was approved by the CMH LMC Research Ethics Committee. Students enrolled in all yearly courses for the MBBS degree were included. The questionnaire consisted of four sections: 1) demographics 2) a table listing 34 potential stressors, 3) the 14-item Perceived Stress Scale (PSS-14), and 4) the Pittsburgh Quality of Sleep Index (PSQI). Data were analyzed in SPSS v. 20. Logistic regression was run to identify associations between group of stressors, gender, year of study, student’s background, stress and quality of sleep. Results: Total response rate was 93.9% (263/280 respondents returned the questionnaire). The mean PSS-14 score was 30.04 (6.97). Logistic regression analysis showed that cases of high-level stress were associated with year of study and academic-related stressors only. Univariate analysis identified 157 cases with high stress levels (59.7%). The mean PSQI score was 8.09 (3.12). According to PSQI score, 203/263 respondents (77.02%) were poor sleepers. Logistic regression showed that mean PSS-14 score was a significant predictor of PSQI score (OR 1.99, P<0.05). Conclusion: We found a very high prevalence of academic stress and poor sleep quality among medical students. Many medical students reported using sedatives more than once a week. Academic stressors contributed significantly to stress and sleep disorders in medical students.
Keywords: Sleep disturbance; Academic stressors; Stress; Perceived stress scale; Pittsburgh Sleep Quality Index; Academic performance; Sleep disturbances; Medical Students